A low viscosity, moisture permeable, acid-etch resistant penetrating sealer and methods of making and using the same

CN121319779BActive Publication Date: 2026-10-27BEIJING UNIV OF CHEM TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511658648.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-13
Publication Date
2026-10-27
Estimated Expiration
2045-11-13

AI Technical Summary

Technical Problem

[0004]本发明的目的之一在于提供一种低粘度、可透湿的防酸蚀渗透加固剂,包含笼型聚倍半硅氧烷(PMOs),易挥发有机溶剂和催化剂,以解决现有技术中砖石文物的保护加固材料成型时间长、与砖石基体相容性差及透湿性不足的问题

Benefits of technology

聚倍半硅氧烷PMOs是一种具有周期性笼型结构的有机硅材料。PMOs粘度低,有利于其渗透进石材表面,防止表面通孔的堵塞。在催化剂作用下PMOs经水解在常温常压下10小时即可形成致密的有机硅固化网络,具有较高强度的同时具备良好的耐酸蚀能力和疏水性。因此,PMOs可用作石材的防酸蚀加固材料。相比于无机加固材料和有机加固涂层,PMOs固化成型快,与主要成分硅酸盐的石材基质相容性好,能有效解决无机加固材料和有机加固涂层存在的技术难点。然而,PMOs固化时间短,可能出现在石材表面少量渗透而完全固化的问题,封闭石材表面的通孔,堵塞水汽的流通。因此,使用合适的易挥发溶剂处理PMOs,进一步降低其粘度的同时防止有机溶剂在石材内部残余,寻找能同时实现水汽良好渗透和防酸雨腐蚀的配比,制备可透湿脆弱砖石文物防酸蚀渗透PMOs加固剂。通过PMOs“小分子疏水结构”的特点,结合低粘度易挥发溶剂的浓度调控,实现了在砖石文物表面的有效渗透与快速固化,解决了砖石文物加固过程中“通孔渗透-疏水耐酸蚀”的技术矛盾。所形成的加固层不仅显著提升耐酸雨能力,而且保持良好的水汽透过性,防止砖石文物表面结冰破坏,同时与硅酸盐石材基体相容性好,不易老化,尤其适用于脆弱砖石文物的紧急与长效防护。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121319779B_ABST
    Figure CN121319779B_ABST
Patent Text Reader

Abstract

The application discloses a low-viscosity, moisture-permeable, acid-erosion-resistant, penetrating and reinforcing agent and a preparation method and use method thereof, and relates to the technical field of cultural relic protection. The acid-erosion-resistant, penetrating and reinforcing agent comprises a cage-shaped polyhedral oligomeric silsesquioxane (PMOs), an easily-volatile organic solvent and a catalyst; by utilizing the "small-molecule hydrophobic structure" characteristics of the PMOs material and combining the regulation of the low-viscosity, easily-volatile solvent, effective penetration and rapid solidification on the surface of masonry cultural relics are realized, and the contradiction between "through-hole penetration" and "hydrophobic acid-erosion resistance" is successfully solved. The formed reinforcing layer not only significantly improves the acid rain resistance, but also maintains good water vapor permeability, prevents the surface of masonry cultural relics from being damaged by icing, and has good compatibility with the silicate stone matrix and is not prone to aging, and is especially suitable for the emergency and long-acting protection of fragile masonry cultural relics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cultural relic protection technology, specifically to a low-viscosity, moisture-permeable acid-resistant and penetrating reinforcing agent, its preparation method, and its application method. Background Technology

[0002] Brick and stone, as the oldest building and art carving materials, constitute a large proportion of various cultural relics in my country. Their non-renewable nature means that damage to these relics has a significant impact on the study of ancient Chinese culture. Among the various forms of damage to brick and stone relics, acid corrosion is the most common, as most are exposed outdoors. Acid rain and other acidic media react with the mineral media (calcium carbonate, silicates, etc.) in the brick and stone, leading to microstructural degradation and further inducing macroscopic mechanical property decline, resulting in surface flaking and other problems. Therefore, finding effective solutions for preventing acid corrosion of brick and stone materials is a major research focus in cultural relic conservation. Currently, inorganic reinforcing agents and hydrophobic organic coatings are the two main methods for acid corrosion prevention and reinforcement.

[0003] Inorganic reinforcing agents are typically mixtures of inorganic salts and organic solvents such as water or alcohols, applied directly to the surface of the stone to be reinforced. Limestone samples treated with a 5% calcium oxalate-acetone / propanol solution form a dense calcium oxalate film on the surface, significantly improving acid and alkali resistance and strength. The samples remain stable in environments with a pH of 3.0–12.0. Using alcohols as solvents and introducing phosphorus and calcium sources, a silicon-substituted hydroxyapatite inorganic cementing phase is generated in situ within the micropores of the stone, significantly improving acid rain resistance. This method is suitable for carbonate rocks (white marble, limestone). Using silica-polydimethylsiloxane composite materials forms a silicate composite network structure in surface cracks, enhancing acid and alkali resistance while maintaining breathability. This prevents ice crystals from accumulating on the material surface under low-temperature conditions due to water vapor impermeability, thus avoiding uneven internal stress and damage to cultural relics. Inorganic reinforcing agents create acid-resistant layers that are less prone to aging and have good compatibility with stone artifacts. However, the curing time is typically several days, making it unsuitable for emergency acid-resistant treatment of brick and stone artifacts. Due to the natural hydrophobic and acid-resistant properties of organic materials, organic coatings can effectively improve the acid resistance of stone. Acrylic polymers and epoxy resins are two commonly used organic coating materials. Using fluorinated acrylic polymers or their emulsions, a dense, hydrophobic, and acid-resistant triple-functional coating is formed on the stone surface after room temperature curing, significantly reducing water absorption and acid penetration rates. Epoxy resin anti-corrosion coatings prepared by adding nano-silica and preservatives to bisphenol A epoxy resin significantly improve the coating's corrosion resistance in oxidizing acidic and alkaline environments and can be used in concrete, cement mortar, and other stone materials. However, organic coatings are prone to aging, and their mechanical properties differ significantly from those of stone artifacts, making it difficult to form a stable acid-resistant reinforcing coating on the stone surface. Furthermore, hydrophobic organic coatings can seal the pores on the stone surface, preventing moisture penetration and causing the surface to freeze easily, which is detrimental to its use at low temperatures. Therefore, it is necessary to develop a new type of protective material to solve the technical difficulties of long molding time of current inorganic reinforcement materials for bricks and stones and poor compatibility and poor moisture permeability of organic reinforcement coatings. Summary of the Invention

[0004] One of the objectives of this invention is to provide a low-viscosity, moisture-permeable acid-resistant and penetrating reinforcing agent, comprising cage-type polysilsesquioxanes (PMOs), volatile organic solvents, and catalysts, to solve the problems of long molding time, poor compatibility with brick and stone matrix, and insufficient moisture permeability in the existing protective and reinforcing materials for brick and stone cultural relics.

[0005] Optionally, the cage-type polysilsesquioxane is one or a combination of side-methoxy polysilsesquioxane, side-ethoxy polysilsesquioxane, and side-isopropoxy polysilsesquioxane.

[0006] Optionally, the volatile organic solvent is one or a combination of petroleum ether, ethanol and ethyl acetate.

[0007] Optionally, the catalyst is an organotin catalyst; preferably, the organotin catalyst is one or a combination of dibutyltin laurate and stannous octoate; more preferably, the organotin catalyst is dibutyltin dilaurate.

[0008] Optionally, the mass fraction of the cage-shaped polysilsesquioxane is 5-20%, preferably 5-10%, more preferably 5%; the mass fraction of the catalyst is 0.3-1%, preferably 1%; and the mass fraction of the volatile organic solvent is 79%-96.7%, preferably 94%.

[0009] The second objective of this invention is to provide a method for preparing the above-mentioned anti-acid corrosion and penetration reinforcing agent, comprising the following steps: dissolving the cage-type polysilsesquioxane in a volatile organic solvent to obtain a PMOs organic solution; before use, adding the catalyst to the PMOs organic solution, mixing evenly, and allowing it to stand at room temperature to obtain the anti-acid corrosion and penetration reinforcing agent.

[0010] Optionally, the preparation method of the above-mentioned anti-acid corrosion and penetration reinforcement agent includes the following steps: dissolving the cage-type polysilsesquioxane (PMOs) in a volatile organic solvent at room temperature (25±2℃) to prepare an organic solution of PMOs with the required mass fraction; before use, adding the curing catalyst according to the mass fraction, stirring evenly, and then letting it stand at room temperature to obtain the anti-acid corrosion and penetration reinforcement liquid.

[0011] Optionally, the above-mentioned acid corrosion and penetration resistant reinforcement agent adopts a two-component storage method of PMO organic solution-catalyst: before use, the PMO organic solution and catalyst must be sealed and dried for storage, and the storage time can be greater than 1 year.

[0012] The third objective of this invention is to provide a method for using an acid-resistant penetrating reinforcement agent, wherein the acid-resistant penetrating reinforcement agent is applied to the surface of a material and penetrates into the surface layer of the material, and the reinforcement is completed after drying in air at room temperature.

[0013] One of the optional methods of use includes the following steps: (1) Using a 1 mL syringe, take the anti-acid corrosion penetrating reinforcement agent, gently touch the surface of the brick and stone artifact, and drop it onto the surface of the brick and stone artifact one drop at a density of 0.1 mL / cm². 2 (2) After drying in the air at room temperature (25±2℃) for 10 hours, the reinforcement is completed, forming a reinforcement layer on the surface of the brick and stone cultural relics; Preferably, in the above method of use: when the anti-acid corrosion penetrating reinforcement agent is dripped onto the surface of the brick and stone cultural relics, the previous drop of anti-acid corrosion penetrating reinforcement agent should be completely penetrated, and the next drop should be added after there is no obvious liquid layer on the surface of the brick and stone cultural relics, so as to control the injection area; Preferably, in the above method of use: the ambient humidity should be kept not higher than 70% during drying.

[0014] Optionally, the material is a brick and stone artifact; preferably, the brick and stone artifact includes stone materials, concrete, cement mortar, plaster and bricks.

[0015] The beneficial technical effects of the present invention are as follows: Polysilsesquioxanes (PMOs) are organosilicon materials with a periodic cage-like structure. PMOs have low viscosity, which facilitates their penetration into the stone surface and prevents clogging of surface pores. Under the action of a catalyst, PMOs can form a dense organosilicon cured network after hydrolysis at room temperature and pressure within 10 hours, exhibiting high strength while possessing good acid resistance and hydrophobicity. Therefore, PMOs can be used as an acid-resistant reinforcement material for stone. Compared to inorganic reinforcement materials and organic reinforcement coatings, PMOs cure quickly and have good compatibility with stone matrices whose main component is silicate, effectively solving the technical difficulties associated with inorganic reinforcement materials and organic reinforcement coatings. However, the short curing time of PMOs may lead to a situation where only a small amount penetrates the stone surface before complete curing, sealing the pores of the stone surface and blocking the flow of moisture. Therefore, by treating PMOs with suitable volatile solvents to further reduce their viscosity while preventing organic solvent residues inside the stone, a formulation that simultaneously achieves good water vapor penetration and acid rain corrosion resistance was sought to prepare a permeable, acid-resistant, and penetrating PMOs reinforcing agent for fragile brick and stone cultural relics. Utilizing the "small molecule hydrophobic structure" of PMOs, combined with the concentration control of low-viscosity volatile solvents, effective penetration and rapid curing on the surface of brick and stone cultural relics were achieved, resolving the technical contradiction of "through-pore penetration - hydrophobic acid resistance" in the reinforcement process of brick and stone cultural relics. The resulting reinforced layer not only significantly improves acid rain resistance but also maintains good water vapor permeability, preventing ice formation and damage to the surface of brick and stone cultural relics. Furthermore, it exhibits good compatibility with silicate stone matrices, is not prone to aging, and is particularly suitable for emergency and long-term protection of fragile brick and stone cultural relics. Attached Figure Description

[0016] Figure 1 This is a schematic diagram illustrating the application method of the anti-acid corrosion and penetration reinforcing agent of the present invention for surface reinforcement of stone cultural relics.

[0017] Figure 2 This is a schematic diagram of the side-methoxylated polysilsesquioxane described in this invention.

[0018] Figure 3 This is a photograph of the anti-acid corrosion and penetration reinforcing agent of Embodiment 1 of the present invention.

[0019] Figure 4 These are photographs illustrating the compressive strength of stone before and after reinforcement using the anti-acid corrosion and penetration reinforcing agent of Example 1 of the present invention.

[0020] Figure 5 This is a schematic diagram showing the compressive strength of stone reinforced with the anti-acid corrosion and penetration reinforcing agent of Examples 1-3 of the present invention.

[0021] Figure 6 These are photographs showing the contact angle of the stone surface after it has been reinforced using the anti-acid corrosion and penetration reinforcing agents of Examples 1-3 of this invention.

[0022] Figure 7 This is a photograph demonstrating the water penetration resistance of a stone surface reinforced with the acid-resistant and penetration-resistant reinforcing agent of Example 1 of the present invention.

[0023] Figure 8 This is a schematic diagram of a testing device for measuring the moisture permeability of stone before and after reinforcement with the anti-acid corrosion and penetration reinforcing agent of Embodiment 1 of the present invention (after standing for two weeks).

[0024] Figure 9 This is a photograph showing the acid rain simulation test of the stone before and after reinforcement with the acid-penetrating reinforcement agent in Example 1 of the present invention (after soaking in acid rain mother liquor for 12 hours).

[0025] Figure 10 This is a photograph of the surface morphology of the stone control group sample after acid rain test treatment in the acid rain resistance test of the present invention.

[0026] Figure 11 These are photographs of the surface morphology of the stone reinforcement samples in Examples 1-3 of the present invention after acid rain test treatment in the surface acid rain resistance test. Detailed Implementation

[0027] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.

[0028] Reference Figures 1 to 11 The low-viscosity, moisture-permeable acid-resistant penetrating reinforcing agent of the present invention comprises cage-type polysilsesquioxanes (PMOs), volatile organic solvents and catalysts, to solve the problems of long molding time, poor compatibility with brick and stone matrix and insufficient moisture permeability of the existing brick and stone cultural relics protection and reinforcement materials.

[0029] The cage-like polysilsesquioxane is one or a combination of side-methoxy polysilsesquioxane, side-ethoxy polysilsesquioxane, and side-isopropoxy polysilsesquioxane; the choice of PMO type depends on the viscosity of the PMO itself, and side-methoxy polysilsesquioxane with lower viscosity is preferred. Its structure is as follows: Figure 2 As shown, it was purchased from Dongyue Fluorosilicon Technology Group Co., Ltd.

[0030] The volatile organic solvent is one or a combination of petroleum ether, ethanol and ethyl acetate; the selection of the volatile organic solvent depends on the viscosity, evaporation rate and effect on the hydrolysis and solidification of PMOs, and is preferably low viscosity (about 0.4 mPa·s), fast evaporation (about 10 mL / min at room temperature) and does not slow down the hydrolysis of PMOs.

[0031] The catalyst is an organotin catalyst; preferably, the organotin catalyst is one or a combination of dibutyltin dilaurate and stannous octoate; to ensure a short curing time and fast curing agent action, the organotin catalyst is more preferably dibutyltin dilaurate.

[0032] The mass fraction of the cage-shaped polysilsesquioxane is 5-20%, preferably 5-10%, and more preferably 5%, to ensure better reinforcement strength, acid corrosion resistance and water vapor permeability of the reinforced stone; the mass fraction of the catalyst is 0.3-1%, preferably 1%, to better accelerate the curing speed; the mass fraction of the volatile organic solvent is 79%-96.7%, preferably 94%.

[0033] The preparation method of the anti-acid corrosion and penetration reinforcement agent according to the present invention includes the following steps: dissolving the cage-type polysilsesquioxane in a volatile organic solvent to obtain a PMOs organic solution; before use, adding the catalyst to the PMOs organic solution, mixing evenly, and allowing it to stand at room temperature to obtain the anti-acid corrosion and penetration reinforcement agent.

[0034] The preparation method of the anti-acid corrosion and penetration reinforcement agent according to the present invention includes the following steps: dissolving the cage-type polysilsesquioxane (PMOs) in a volatile organic solvent at room temperature (25±2℃) to prepare an organic solution of PMOs with the required mass fraction; before use, adding a curing catalyst according to the mass fraction, stirring evenly, and then letting it stand at room temperature to obtain the anti-acid corrosion and penetration reinforcement liquid.

[0035] The storage method of the acid corrosion and penetration resistance reinforcement agent of the present invention using a two-component PMO organic solution-catalyst is as follows: before use, the PMO organic solution and catalyst must be sealed and dried for storage, and the storage time can be greater than 1 year.

[0036] The method of using the anti-acid corrosion penetration reinforcing agent according to the present invention is as follows: the anti-acid corrosion penetration reinforcing agent is applied to the surface of the material and penetrates into the surface layer of the material, and the reinforcement is completed after drying in air at room temperature.

[0037] In a preferred embodiment, one of the optional methods of use is described below. Figure 1 The steps include: (1) Using a 1mL syringe, take an anti-acid corrosion penetrating reinforcement agent, gently touch the surface of the brick and stone artifact, and drop it onto the surface of the brick and stone artifact one drop at a density of 0.1 mL / cm³. 2(2) After drying in air at room temperature (25±2℃) for 10 hours, the reinforcement is completed, forming a reinforcement layer on the surface of the brick and stone artifacts; preferably, in the above method of use: when the anti-acid corrosion penetrating reinforcement agent is dripped onto the surface of the brick and stone artifacts, the previous drop of anti-acid corrosion penetrating reinforcement agent should be completely penetrated, and the next drop should be added after there is no obvious liquid layer on the surface of the brick and stone artifacts, so as to control the injection area; preferably, in the above method of use: the ambient humidity should be kept not higher than 70% during drying. The material can be brick and stone artifacts; preferably, the brick and stone artifacts include stone materials, concrete, cement mortar, grout and bricks.

[0038] The following detailed description, in conjunction with specific embodiments, illustrates the low-viscosity, moisture-permeable acid-resistant penetrating reinforcing agent of the present invention, its preparation method, usage method, and application.

[0039] Main raw materials and equipment used: Unless otherwise specified, the raw materials and equipment used in each embodiment and comparative example are the same; the raw materials used in the embodiments and comparative examples are disclosed in the prior art unless otherwise specified, such as those that can be directly purchased or prepared according to the preparation methods disclosed in the prior art, and no specific restrictions are imposed.

[0040] Example 1 Take 10.50 g of petroleum ether (boiling point 60~90℃, Beijing Chemical Plant) and add side-methoxy polysilsesquioxane (approximately 29 mPa·s, its structure is as follows). Figure 2 As shown, 0.56g of dibutyltin dilaurate (Sigma-Aldrich, 95%) was purchased from Dongyue Fluorosilicon Technology Group Co., Ltd. The solution was shaken in a glass bottle for 30 seconds, then 0.11g of dibutyltin dilaurate (Sigma-Aldrich, 95%) was added, shaken for 30 seconds, and allowed to stand at 25°C for 2 hours to obtain 11.17g (5wt%) of anti-acid corrosion penetration reinforcing agent. Figure 3 As shown.

[0041] Example 2 Take 8.90g of petroleum ether (boiling point 60~90℃, Beijing Chemical Plant), add 1.00g of side-methoxy polysilsesquioxane (Dongyue Fluorosilicon Technology Group Co., Ltd.), shake in a glass bottle for 30 seconds, then add 0.10g of dibutyltin dilaurate (Sigma-Aldrich, 95%), shake for 30 seconds, and let stand at 25℃ for 2 hours to obtain 10.0g (10wt% concentration) of anti-acid corrosion penetration reinforcing agent.

[0042] Example 3 Take 9.60g of petroleum ether (boiling point 60~90℃, Beijing Chemical Plant), add 2.43g of side-methoxy polysilsesquioxane (Dongyue Fluorosilicon Technology Group Co., Ltd.), shake in a glass bottle for 30 seconds, then add 0.12g of dibutyltin dilaurate (Sigma-Aldrich, 95%), shake for 30 seconds, and let stand at 25℃ for 2 hours to obtain 12.15g (20wt% concentration) of anti-acid corrosion penetration reinforcing agent.

[0043] Performance testing The compressive strength, surface hydrophobicity, and surface acid resistance of stone samples were tested before and after reinforcement with an anti-acid corrosion penetrating reinforcing agent.

[0044] Stone compressive strength test: The stone bricks were cut into test specimens using a hacksaw, with dimensions of 10mm × 10mm × 20mm. The specimens are shown below. Figure 4 As shown.

[0045] Using a 1 mL syringe, 1 mL of the 5% concentration acid-penetrating reinforcing agent from Example 1 was dripped onto the surface of each test sample from the center. The sample was then allowed to air dry at 25°C for at least 10 hours. A sample without the reinforcing agent was used as a control. The compressive strength of the reinforced stone sample was 5.6 MPa, while the compressive strength of the control group was 4.5 MPa. Figure 5 As shown in the figure. The results indicate that the compressive strength of the sample increased by 19.6% after reinforcement.

[0046] Using a 1 mL syringe, take 1 mL of the 10% concentration acid-penetrating reinforcing agent from Example 2 and drip it onto the surface of each surface of the test sample. Allow the sample to air dry at 25°C for at least 10 hours. Use a sample without the reinforcing agent as a control before starting the test. The compressive strength of the reinforced stone sample is 6.3 MPa. Figure 5 As shown in the figure. The results indicate that the compressive strength of the sample increased by 40% after reinforcement.

[0047] Using a 1 mL syringe, take 1 mL of the 20% concentration acid-penetrating reinforcing agent from Example 3 and drip it onto the surface of each surface of the test sample. Allow the sample to air dry at 25°C for at least 10 hours. Use a sample without the reinforcing agent as a control before starting the test. The compressive strength of the reinforced stone sample is 6.7 MPa. Figure 5 As shown in the figure, the results indicate that the compressive strength of the sample increased by 48.9% after reinforcement.

[0048] The results of the stone compressive strength test prove that PMOs reinforcing agent has a good reinforcing effect on stone.

[0049] Surface hydrophobicity: The stone bricks were cut into test pieces using a hacksaw, with a test area of ​​15mm × 20mm.

[0050] Using a 1 mL syringe, 0.2 mL of the 5% concentration acid-penetrating reinforcement agent from Example 1 was dripped onto the surface of the test sample from the center. The sample was then allowed to air dry at 25°C for at least 10 hours. A sample without the reinforcement agent was used as a control for the initial testing. The hydrophobicity of the sample was characterized by the surface water contact angle, which was measured using a water contact angle meter (Shanghai Zhongchen). Before reinforcement, water spread instantly upon contact with the sample, showing hydrophilicity. After reinforcement, the water contact angle increased to 113.5°, exhibiting significant hydrophobicity. Figure 6 As shown.

[0051] Using a 1 mL syringe, 0.2 mL of the 10% concentration acid-penetrating reinforcement agent from Example 2 was dripped onto the surface of the test sample from the center. After air drying at 25°C for at least 10 hours, the water contact angle increased to 133.5°, exhibiting significant hydrophobicity. Figure 6 As shown.

[0052] Using a 1 mL syringe, 0.2 mL of the 20% concentration acid-penetrating reinforcement agent from Example 3 was dripped onto the surface of the test sample from the center. After air drying at 25°C for at least 10 hours, the water contact angle increased to 136.5°, exhibiting significant hydrophobicity. Figure 6 As shown.

[0053] It can be seen that the strong hydrophobic effect of polysilsesquioxane is beneficial in preventing water penetration, such as... Figure 7 As shown, this prevents damage to the stone caused by water freezing in low-temperature environments.

[0054] Water vapor permeability of stone samples: The moisture permeability of the material was tested using the permeability cup method to obtain the moisture permeability of the samples before and after reinforcement. The permeability cup method apparatus is as follows: Figure 8 As shown, a circular stone sample (5 mm thick) was placed on a 58 mm diameter glass petri dish. Tap water was added to the petri dish, with the liquid level 10 mm below the top of the stone sample. The mass of the petri dish containing tap water was recorded. After the test equipment was left to stand in a room with an average temperature of 20°C for one week, the mass of the petri dish containing tap water was again recorded. The mass difference before and after the standing period was calculated to obtain the mass of water vapor permeation. The stone moisture permeability was calculated as a percentage, based on the ratio of the mass of water vapor permeation to the covered area.

[0055] Using a 1 mL syringe, 2.6 mL of the 5% concentration anti-acid corrosion penetrating reinforcement agent from Example 1 was dripped onto the surface of the test sample from the center. The sample was then allowed to air dry at 25°C for at least 10 hours. The moisture permeability of the reinforced stone sample and the untreated control sample was then measured. The moisture permeability of the stone sample was 0.234 g / cm³. 2 The moisture permeability of the control group was 0.404 g / cm³.2 The moisture permeability of the reinforced stone sample was 57.9% of that before reinforcement, indicating that it still has good water vapor permeability.

[0056] Using a 1 mL syringe, 2.6 mL of the 10% concentration acid-penetrating and reinforcing agent from Example 2 was dripped onto the surface of the test sample from the center. The sample was then allowed to air dry at 25°C for at least 10 hours. The moisture permeability of the reinforced stone sample and the untreated control sample was then measured. The moisture permeability of the stone sample was 0.169 g / cm³. 2 The moisture permeability of the control group was 0.404 g / cm³. 2 The moisture permeability of the reinforced stone sample was 41.8% of that before reinforcement, indicating that it still has good water vapor permeability.

[0057] Using a 1 mL syringe, 2.6 mL of the 20% concentration anti-acid corrosion penetrating reinforcement agent from Example 3 was dripped onto the surface of the test sample from the center. The sample was then allowed to air dry at 25°C for at least 10 hours. The moisture permeability of the reinforced stone sample and the untreated control sample was then measured. The moisture permeability of the stone sample was 0.146 g / cm³. 2 The moisture permeability of the control group was 0.404 g / cm³. 2 The moisture permeability of the reinforced stone sample was 36.1% of that before reinforcement, indicating that it still has good water vapor permeability.

[0058] Surface acid rain resistance: The stone bricks were cut into test samples with a test area of ​​15mm × 20mm using a hacksaw. 0.2 mL of the acid-resistant penetrating reinforcing agent from Examples 1-3 was dripped onto the surface of the test sample from the center using a 1mL syringe. The sample was then allowed to air dry at 25°C for at least 10 hours. A sample without the reinforcing agent was used as a control. The acid rain resistance of the samples was simulated using a wet-dry alternating method.

[0059] Acid rain simulation stock solution was prepared using concentrated sulfuric acid (18.4 mol / L, Beijing Chemical Plant). 20 μL of concentrated sulfuric acid was added to deionized water, and 100 mL of solution was prepared with deionized water to obtain the acid rain simulation stock solution. The pH of the stock solution was verified to be approximately 2 using Guangfa pH test paper. 5 mL of the stock solution was dropped into the center of a 100 mm diameter plastic petri dish. Two sets of samples, before and after reinforcement with the anti-acid corrosion penetration reinforcing agent from Example 1, were placed upside down in the acid rain stock solution in the two petri dishes. After sealing and standing for 12 hours, the samples were removed, with the side in contact with the stock solution facing upwards, and placed in the air. Figure 9 As shown, due to the hydrophobicity of polysilsesquioxane, the polysilsesquioxane-reinforced area is clearly visible. After air drying for at least 12 hours, the surface of the sample after the simulated test treatment was observed under a super depth-of-field microscope (Recar DM4M). As a control group, obvious salt precipitation crystals appeared on the surface, indicating the erosion caused by acid rain. Figure 10As shown, no salting-out crystals appeared on the surfaces of the samples reinforced with the 5%, 10%, and 20% concentrations of the acid-penetrating reinforcing agent from Examples 1-3, proving that the polysilsesquioxane reinforcement strategy can effectively resist acid rain erosion. Figure 11 As shown.

[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. The protection scope of this application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims. Therefore, the protection scope of this application should be determined by the protection scope of the claims.

Claims

1. A low-viscosity, moisture-permeable acid-resistant and penetrating reinforcing agent, characterized in that, It is composed of cage-like polysilsesquioxane, a volatile organic solvent, and a catalyst; the cage-like polysilsesquioxane is one or a combination of side-methoxy polysilsesquioxane, side-ethoxy polysilsesquioxane, and side-isopropoxy polysilsesquioxane; the volatile organic solvent is one or a combination of petroleum ether, ethanol, and ethyl acetate; the catalyst is an organotin catalyst; the mass fraction of the cage-like polysilsesquioxane is 5-20%, the mass fraction of the catalyst is 0.3-1%, and the mass fraction of the volatile organic solvent is 79%-96.7%.

2. The acid-resistant and penetrating reinforcing agent as described in claim 1, characterized in that, The organotin catalyst is one or a combination of dibutyltin cinnamate and stannous octoate.

3. The acid-resistant and penetrating reinforcing agent as described in claim 1, characterized in that, The cage-shaped polysilsesquioxane has a mass fraction of 5%, the catalyst has a mass fraction of 1%, and the volatile organic solvent has a mass fraction of 94%.

4. The method for preparing the acid-resistant and penetrating reinforcing agent according to any one of claims 1-3, characterized in that, The process includes the following steps: dissolving the cage-type polysilsesquioxane in a volatile organic solvent to obtain a PMOs organic solution; before use, adding the catalyst to the PMOs organic solution, mixing evenly, and allowing it to stand at room temperature to obtain an acid-resistant and penetrating reinforcing agent.

5. The method of using the anti-acid corrosion and penetration reinforcing agent as described in any one of claims 1-3, characterized in that, The acid-resistant penetrating reinforcing agent is applied to the material surface and penetrates into the surface layer of the material. The reinforcement is completed after drying in air at room temperature.

6. The method of using the acid-resistant and penetrating reinforcing agent as described in claim 5, characterized in that, The material in question is a brick and stone artifact.

7. The method of using the acid corrosion and penetration resistant reinforcing agent as described in claim 6, characterized in that, The brick and stone artifacts include stone materials, concrete, cement mortar, and bricks.

Citation Information

Patent Citations

  • Cage-type POSS-linear siloxane hybrid material suitable for sandstone cultural relic protection, and preparation method and application thereof

    CN113717387A